PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN MEDIA GRAFIS DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS V SDN TANJUNGREJO TAHUN AJARAN 2015/2016 - RIKARDO, DAVID PRIMA (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Numbered Heads Together (NHT) Cooperative Model Using Graphic Media in Improving Social Science Learning for the Fifth Grade Students of SD Negeri Tanjungrejo in the Academic Year of 2015/2016. The objectives of this research is to improve social science learning for the fifth grade students. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. The results of this research showed that the application of Numbered Heads Together (NHT) cooperative model using graphic media can improve social science learning for the fifth grade students of SD Negeri Tanjungrejo in the academic year of 2015/2016. Keywords: Numbered Heads Together (NHT), graphic media, social science learning Abstrak: Penerapan Model Kooperatif Tipe Numbered Heads Together (NHT) dengan Media Grafis dalam Peningkatan Pembelajaran IPS pada Siswa Kelas V SDN Tanjungrejo Tahun Ajaran 2015/2016. Tujuan dari penelitian ini adalah meningkatkan pembelajaran IPS pada siswa kelas V. Penelitian ini dilaksanakan dalam tiga siklus terdiri dari perencanaan, pelaksanaan, observasi dan refleksi. Hasil penelitian ini menunjukkan bahwa penerapan model kooperatif tipe Numbered Heads Together (NHT)dengan media grafis dapat meningkatkan pembelajaran IPS pada siswa kelas V SDN Tanjungrejo tahun ajaran 2015/2016. Kata Kunci : Numbered Heads Together (NHT), Media Grafis, Pembelajaran IPS